2022
DOI: 10.1007/s11332-022-00999-w
|View full text |Cite
|
Sign up to set email alerts
|

Injuries in Canadian high school boys’ collision sports: insights across football, ice hockey, lacrosse, and rugby

Abstract: Background Collision sport participation rates among high school youth in Canada are high. While participation is beneficial for physical and mental well-being, the rates of injury in these sports are high. Aims This study aims to compare injury rates and profiles across four common youth collision sports (ice hockey, tackle football, lacrosse, rugby). Methods Data from a cross-sectional questionnaire of 2029 high s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…[15][16][17] Subjectively, players have reported more any injury occurrence during contact with a larger player than them in boy's collision sports. 27 Nonetheless, information gained from this study has the potential to inform the formulation and design of shoulder injury prevention strategies and future body checking policies that will make youth sport a safer space for youth ice hockey players.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Subjectively, players have reported more any injury occurrence during contact with a larger player than them in boy's collision sports. 27 Nonetheless, information gained from this study has the potential to inform the formulation and design of shoulder injury prevention strategies and future body checking policies that will make youth sport a safer space for youth ice hockey players.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, history of sport related concussions was most frequently reported in ice hockey, which is consistent in the literature. 3,5 Collegiate athletes most frequently sought knowledge within their collegiate athlete network. Those with a concussion history sought knowledge from the university athletic trainer and health services, aligning with help seeking knowledge from medical professionals when an collegiate athlete is injured.…”
Section: Discussionmentioning
confidence: 99%
“…2 The incidence of collision sport concussions in Canadian high school boys ranges from 12.4 to 15.8 concussions per 100 athletes per year; largely due to contact with another player. 3 The rate of all sport related concussions has been reported to be higher among male and female collegiates versus high school athletes. 4 Furthermore, the highest rates of concussion in collegiate sports by gender are found in men's ice hockey and women's soccer.…”
Section: Introductionmentioning
confidence: 99%
“…We do not dispute the significance of concussions within rugby given the inherent nature of the high-impact contact and collision sport (16). The concussion rate among both male and female high school rugby players is high and often the result of tackle events during competition (17)(18)(19)(20)(21). At the community level, research found that 37.2% of a sample of Canadian senior rugby players reported experiencing concussion symptoms over the past season, 87% of which were formally diagnosed with a concussion (22).…”
mentioning
confidence: 99%